HUBUNGAN JENIS APLIKASI GADGET TERHADAP PERKEMBANGAN ANAK USIA PRA SEKOLAH DI KECAMATAN WELERI - Sulastri Sulastri; Sri Hesthi Sonyo Rini (LPPM STIKES Muhammadiyah Kendal, 2022)
The continued use of gadgets has a negative impact on the mindset and behavior of children in their daily lives, children who tend to use gadgets continuously will be very dependent and become routine activities in daily activities, in this case children often prefer playing gadgets, causing children to be lazy to move and do activities. Knowing the relationship between types of gadget applications on the development of toddlers and school age in Weleri District. Quantitative research with survey design. This research is a post test design. The sample in this study were 31 respondents. The sampling technique was simple random sampling technique. Univariate analysis produces distributions and percentages and bivariate analysis using chi-square. Results: The results showed that most of the cellphones played on the YouTube application type. The results showed that the majority experienced the appropriate development. There is a relationship between the type of application on the development of pre school in Weleri District, Kendal Regency